Peran Kelompok Tani Terhadap Peningkatan Produktivitas Usahatani Sawi di Pontianak Utara - Kristina Eda; Novira Kusrini; Shenny Oktoriana (University of Jember, 2023)
The problem currently faced by mustard greens farming is fluctuations in production due to erratic weather, causing pest attacks and drought which lead to crop failures. This study aims to analyze the level of the role of farmer groups and how the correlation of the role of farmer groups to the productivity of mustard cultivation in North Pontianak. Data was collected through interviews and filling out questionnaires to 75 farmers belonging to farmer groups using the Simple Random Sampling technique. The research method used is descriptive method and analyzed using rank spearman. The result showed that has been carried out, the level of the role of farmer groups seen from the aspects of class learning (x1), vehicle for cooperation (x2), and production units (x3) have a substantial (not close) and unidirectional relationship to productivity.